Occult cytomegalovirus cholangitis as a potential cause of cholestatic complications after orthotopic liver transplantation?: A study of cytomegalovirus DNA in bile - Gotthardt, Daniel; Senft, Jonas; Sauer, Peter; Weiss, Karl Heinz; Flechtenmacher, Christa; Eckerle, Isabella; Schaefer, Yvonne; Schirmacher, Peter; Stremmel, Wolfgang; Schemmer, Peter; Schnitzler, Paul (Liver transplantation, 2013)
Cholestatic complications, important causes of morbidity and mortality after orthotopic liver transplantation (OLT), often have an unclear etiology. Human cytomegalovirus (CMV) infections occur in immunosuppressed patients and can be detected in blood samples. However, CMV analyses of body fluids and biopsies are more sensitive. Here we evaluated whether a CMV analysis of bile could reveal occult CMV cholangitis. We evaluated OLT patients undergoing endoscopic retrograde cholangiography (ERC) for suspected biliary complications after OLT at a tertiary care center. Biliary CMV DNA levels were measured with real-time polymerase chain reaction. A nonanastomotic biliary lesion (NABL) group consisted of patients with nonanastomotic strictures (NASs) at the time of ERC (n = 59) and patients with normal ERC findings but microscopic biliary lesions in biopsy samples (n = 12). The anastomotic stricture (AS) group comprised patients with ASs only (n = 53). In all, 124 OLT patients underwent 240 ERC procedures. Biliary CMV DNA was detected in 14 of the 124 patients and was more frequently found in the NABL group (12/71 for the NABL group versus 2/53 for the AS group, P = 0.02). Concurrent sampling of CMV DNA in blood yielded negative results. Biliary CMV was more frequently detected in patients with a positive recipient status (13/73 or 17.8% versus 1/44 or 2.3%, P < 0.05). There was no significant difference in the incidence of biliary CMV between patients with a high-risk CMV status and patients with a low-risk CMV status. The median interval between OLT and biliary CMV detection was 8.4 months (range = 0.4-212.8 months). In conclusion, biliary CMV was detected in a substantial number of patients after OLT and was significantly associated with NASs or microscopic biliary lesions. A potential occult CMV infection could, therefore, be considered as a contributory etiological factor in the development of biliary complications. Liver Transpl 19:1142-1150, 2013. © 2013 AASLD.